Answer:
113/24
Step-by-step explanation:
Simplify the following:
(14 + 1/8)/3
Put 14 + 1/8 over the common denominator 8. 14 + 1/8 = (8×14)/8 + 1/8:
((8×14)/8 + 1/8)/3
8×14 = 112:
(112/8 + 1/8)/3
112/8 + 1/8 = (112 + 1)/8:
((112 + 1)/8)/3
112 + 1 = 113:
(113/8)/3
113/8×1/3 = 113/(8×3):
113/(8×3)
8×3 = 24:
Answer: 113/24
Answer:
f(2) = 9
Step-by-step explanation:
It's give in the question,
Two different functions are,
f(x) = 4x + 1
g(x) = -2x
Then we have to find the output value of function 'f' for the input value x = 2.
By substituting the value of x in the function 'f',
f(2) = 4(2) + 1
= 9
f(2) = 9
Answer:
-59/12
Step-by-step explanation:
finish whats inSide brackets first
so -12+3 =-9
-9*1/4 will be next and = -9/4
9/4+8/3 =. 59 /12
Answer:
19
Step-by-step explanation:
ok is this just a joke?
nine plus ten
9 + 10 = 19
The property shown in the following equation is 9 beacause simply we know 9=1 +8 so its easy